استقصاء بعض مشكلات الطالب الجامعي في ضوء بعض المتغيرات (دراسة ميدانية - فلوح, احمد (University of Eloued جامعة الوادي, 2019)
هدفت الدراسة إلى التعرف على بعض مشكلات الطالب الجامعي في من وجهة نظر الطلبة، و التعرف على اثر متغير الجنس، ومتغير التخصص على استجابات الطلبة. ولتحقيق أهداف الدراسة تم تطبيق استبيان على عينة مكونة من طلبة الجامعة. وأسفرت نتائج الدراسة: أن الطالب الجامعي يعاني بدرجة مرتفعة من مشكلات أكاديمية، ومشكلات المحيط المرتبطة بالجانب الأكاديمي، ومن مشكلات اقتصادية. ووجد فرق دال إحصائيا بين الذكور والإناث في تقديرهم للمشكلات، بينما كشفت الدراسة انه لا يوجد فرق دال إحصائيا يعزى للتخصص. الكلمات المفتاحية: الطالب الجامعي، المشكلات، المشكلات الأكاديمية، المشكلات الاقتصادية والمالية، مشكلات المحيط المرتبطة بالجناب الأكاديمي. Investigating some problems of university students in the light of some variables (A field study) Abstract : The study aimed to identify some problems of university students from the point of view of students, and to identify the impact of the variable sex, and the variable specialization on the responses of students. To achieve the objectives of the study, a questionnaire was applied to a sample of university students. The results of the study: that the university student suffers a high degree of academic problems, ocean problems associated with the academic side, and economic problems. There was a statistically significant difference between males and females in their assessment of problems, while the study revealed that there was no statistically significant difference due to specialization. Keywords: University student, problems, academic problems, economic and financial problems, ocean problems associated with academic side
Investigating some problems of university students in the light of some variables (A field study)
مجلة الدراسات والبحوث الاجتماعية المجلد 07 العدد 01 جامعة الوادي
Keywords: الطالب الجامعي، المشكلات، المشكلات الأكاديمية، المشكلات الاقتصادية والمالية، مشكلات المحيط المرتبطة بالجناب الأكاديمي.; University student, problems, academic problems, economic and financial problems, ocean problems associated with academic side.